KONSEP KHITBAH DALAM ISLAM - Mustakim, Ahmad; Kholipah, Nurul (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
In Islam, the issue of marriage is one of the urgent issues regulated in various teachings. The Qur'an and as-Sunnah, the two main sources of Islamic teachings, have much to say on this issue. One of the problems related to premarital issues is the issue of khitbah, namely the proposal (to apply) or the meaning of asking a woman to marry in a way and media commonly known in the community. Khitbah is the process of asking for approval from a woman to become a wife to a man or a man's request for a woman to be a prospective wife. This article focuses on the study of the concept of khitbah in Islam which explains the limitations or issues that need to be done before marriage (premarital). The purpose of this article is to provide khitbah guidelines in the view of Islam to people who are about to get married, so that they are in accordance with Islamic law. As for the types of sermons, there are direct (clear and indirect speech, namely by using sarcastic speech. In making a proposal, you should do it politely and in accordance with local customs. There are several provisions that the suitor needs to know when making a proposal Namely: 1) The suitor may see the woman being proposed to the extent permitted by syara', such as the face and palms. The reason is because by looking at the woman he is marrying will provide a guarantee for the continuity of the husband and wife relationship. 2) Recognize the characteristics of the candidate he is proposing. As well as knowing his face, a suitor also has the right to know the character of the candidate he is proposing. However, in this case the suitor may only ask people close to women. 3) The suitor and the woman he proposes cannot be alone together.